An Analysis of Indonesian Spelling Errors in Short Stories Written by Eleventh-Grade Students at SMA Nurul Ibrahimi Rantauprapat - Juli Yani; F. Ferdiawan; Imam Tazali; Hadi Wibowo; Khoerotun Nisa Liswati (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study analyzes errors in the use of Indonesian spelling in short story texts written by eleventh-grade students at SMA Nurul Ibrahimi. Common errors include the incorrect use of capital letters and punctuation that do not align with the General Guidelines for Indonesian Spelling (PUEBI). The causes of these errors include a limited understanding of spelling rules, the influence of informal language, and a lack of writing practice. This study employs a descriptive qualitative approach, with primary data consisting of students’ short story texts and secondary data from relevant literature. The results show frequent errors in the use of capital letters at the beginning of sentences, in names, and in place names. Punctuation errors often involve the use of commas, periods, and quotation marks. The study recommends practice-based learning to improve students’ skills in using correct spelling.